Lung imaging in bronchopulmonary dysplasia: a systematic review. (September 2020) - Vanhaverbeke, K.; Van Eyck, A.; Van Hoorenbeeck, K.; De Winter, B.; Snoeckx, A.; Mulder, T.; Verhulst, S.
Abstract: Background: Bronchopulmonary dysplasia (BPD) remains a common complication of preterm birth. Both historically and in current practice, radiologic evaluation of the lungs has an important role in assessing disease severity and complications. Aim: To provide an overview of imaging techniques for detecting lung abnormalities in patients with BPD in all age ranges. Methods: A systematic literature search was conducted in PubMed, Web of Science and the Cochrane Library. Records were screened by title and abstract and then by full text. A total of 37 records were selected and included in this qualitative literature overview. Results: Computed tomography (CT) was the most commonly used imaging modality, followed by chest radiography and magnetic resonance imaging (MRI). Several qualitative and quantitative scoring systems were presented and most showed good correlation with BPD severity. The association with functional and clinical outcomes was only rarely reported, showing varying correlation with spirometry results and respiratory exacerbations. MRI is an upcoming imaging technique for BPD that is technically feasible, showing clear differences in the lung parenchyma of patients with BPD. Conclusion: Several imaging and scoring methods indicate that lung imaging continues to play a role in BPD care. Standardization and correlation with functional and clinical outcomes will become increasingly important for further research. Highlights: Lung imaging is an important tool to assess structural and functional changes in BPD CT remains the most commonly used imaging technique and allows meticulous anatomical assessment MRI is a promising, feasible and non-ionizing alternative to image the BPD lung Scoring systems are an important tool in the assessment of lung images in BPD Structural changes are typical of BPD, but their relationship with clinical outcome requires further research